Peran Orang Tua dalam Pendidikan Agama Kristen Menurut Kitab Amsal Bagi Anak Usia 7-12 Tahun - Paulus Kunto Baskoro; Hardi Budiyana (Sekolah Tinggi Teologi Tenggarong, 2021)
Family is the most comfortable palce in a chlid’s education. Because children have a lot of time in a family. Chlirdren’s education is the most important part in life in the future. Especially in Christian religious education. Parents must play an active role in educating their their children to grow spiritually in Christ. Christian regilious education for children cannot be ruled out. Some parents think that their children’s education in Christianity is not primary. As evidenced by several cases, parents are more focused on work, career, position rather than focusing on Christian religious education. Some also stated that the role of educating children could be left to the church. Trough this wiritng, the author would like to remind again how important the role of parents for Christian religious education for their children aged 7-12 years according to the Book of Provebs. This writing uses the mothed of descriptive literature. The goal is that through writing, First, to awaken every Christian parent to play an active role in Christian religious education for their children. Second, parents practice the role system of Christian religious education for children according to Bible truth. Third, children of believers experience early spiritual growth, so that their future is strong in God.Abstrak:Keluarga adalah tempat yang paling nyaman dalam sebuah pendidikan anak. Sebab anak memiliki banyak waktu dalam sebuah keluarga. Pendidikan anak merupakan bagian terpenting dalam kehidupan di masa depan. Terutama dalam pendidikan agam Kristen. Orang tua harus berperan aktif dalam mendidik anaknya untuk bertumbuh secara rohani dalam Kristus. Pendidikan agama Kristen terhadap anak, tidak bisa dikesampingkan begitu saja. Beberapa orang tua menganggap bahwa pendidikan anak pada agama Kristen adalah hal yang tidak primer. Terbukti dengan beberapa kasus yang terjadi, orang tua lebih fokus kepada pekerjaan, karir, jabatan daripada fokus kepada pendidikan agama Kristen. Beberapa juga menyatakan bahwa peran mendidik anak bisa diserahkan kepada gereja. Lewat penulisan ini, penulis mau kembali mengingatkan betapa pentingnya peran orang tua bagi pendidikan agama Kristen bagi anak-anaknya di usia 7-12 tahun menurut Kitab Amsal. Penulisan ini menggunakan metode deskritif literatur. Tujuannya supaya lewat penulisan yaitu Pertama, menyadarkan setiap orang tua Kristen untuk berperan aktif dalam pendidikan agama Kristen terhadap anak. Kedua, orang tua mempraktekkan sistem peran pendidikan agama Kristen bagi anak menurut kebenaran Alkitab. Ketiga, anak-anak orang percaya mengalami pertumbuhan rohani secara dini, sehingga masa depan mereka kuat di dalam Tuhan.